PENINGKATAN LITERASI MIKROPLASTIK DAN PENERAPAN AUSDRISK TOOLS DALAM PENCEGAHAN RESIKO DIABETES TIPE 2 PADA IBU MAJELIS TAKLIM DI KAMPUNG KAPUK JAKARTA SELATAN - Anita Sukarno; Erna Veronika; Yulia Wahyuni; Meisya Talahaturuson; Fransiskus Febri Juferta Telaumbanua; Mayliana Perangin Angin; Yunarti Yosefa M. Manec; Inggrid Tabalessy (Jurnal Abdi Insani, 2023)
Approximately 35% of the women of the Taklim At Taqwa Council suffer from hypertension and an increase in type 2 diabetes. Housewives are the heart of household life with big tasks, such as nurses and guarantors of nutrition for family members, and have the role of the main madrasah or first educator for children. his son. Empowerment of women is a major milestone in achieving optimal health and well-being for the family unit by increasing equality of access to health literacy. First, increase the ability to detect the risk of type 2 diabetes and literacy of mothers about microplastics and their negative impact on health, especially the risk of chronic disease and the ability to regulate diabetes nutritional patterns. The partner of the Community Partnership Program (PKM) is the Chairman of the Taklim Council At Taqwa Kampung Kapuk Lebak Bulus Village. This activity takes place from July to August 2023 in 5 stages, namely surveying problems, training on using AUSDRISK TOOLS in detecting the risk of type 2 diabetes, introducing microplastics, regulating the nutritional pattern of diabetics, and monitoring the evaluation of activities. This activity can increase partners' knowledge and skills in using instruments to detect the risk of type 2 diabetes, be able to read the numbering of plastic materials and identify safe plastic containers, and demonstrate the division of nutritional components of diabetes and making smoothies as a healthy snack for diabetics. Through this activity partners gain increased knowledge in detecting the risk of type 2 diabetes, the ability to identify safe plastic containers and prevent exposure to microplastics as well as the ability to regulate diabetic nutritional patterns.